Implementasi Sistem Peringatan Banjir Dini dengan Sensor HC-SR04 Berbasis ESP32 Internet of Things - Sujono, Sujono; Rusli M, Muhammad (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
Floods are natural disasters that often occur in Indonesia and sometimes cause great material and human losses. This paper describes the design and implementation of an IoT-based flood early warning system using ESP32 microcontroller and HC-SR04 ultrasonic sensor technology. The system is capable of automated river water level measurements at 5 minutes interval with real-time data sent to a web-based monitoring dashboard. Field validation was conducted in a quantitative experimental study at a river dam facility located in Jombang Regency. Performance testing results show that the system has high reliability, achieving 98.63% data transmission success rate. The HC-SR04 sensor has measurement accuracy of 97.69% with Mean Absolute Error (MAE) value equal to 2.31%. The warning mechanism works by comparing the water level with certain thresholds so that the dashboard can display safe or alert status conditions based on measurements made by the HC-SR04 sensor. Experimental results prove that this system is effective and economically feasible as a flood early warning solution for vulnerable regions, enhancing disaster preparedness capabilities significantly.